2014
DOI: 10.1371/journal.pone.0085264
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Differences between Circulating Tumor Cells from Prostate Cancer Patients and Cultured Prostate Cancer Cells

Abstract: Circulating tumor cell (CTC) enumeration promises to be an important predictor of clinical outcome for a range of cancers. Established CTC enumeration methods primarily rely on affinity capture of cell surface antigens, and have been criticized for underestimation of CTC numbers due to antigenic bias. Emerging CTC capture strategies typically distinguish these cells based on their assumed biomechanical characteristics, which are often validated using cultured cancer cells. In this study, we developed a softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
116
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 52 publications
6
116
2
1
Order By: Relevance
“…32) In contrast to their normal cell counterparts/ hematologic cells, cancer cells have been reported to differ cytomorphologically e.g., cancer cells exhibit a higher nuclear cytoplasmic ratio, variable size, abnormal nuclear DNA content etc. [33][34] Cytomorphological deformities in CTC has been correlated to a poor clinical outcome in colorectal, prostate and metastatic breast cancers. 35) To overcome the limitation of size-based enrichment methods, additional approaches should be used to increase the probability/efficacy of CTC detection/capture.…”
Section: Biological and Pharmaceutical Bulletin Advance Publication Bmentioning
confidence: 99%
See 1 more Smart Citation
“…32) In contrast to their normal cell counterparts/ hematologic cells, cancer cells have been reported to differ cytomorphologically e.g., cancer cells exhibit a higher nuclear cytoplasmic ratio, variable size, abnormal nuclear DNA content etc. [33][34] Cytomorphological deformities in CTC has been correlated to a poor clinical outcome in colorectal, prostate and metastatic breast cancers. 35) To overcome the limitation of size-based enrichment methods, additional approaches should be used to increase the probability/efficacy of CTC detection/capture.…”
Section: Biological and Pharmaceutical Bulletin Advance Publication Bmentioning
confidence: 99%
“…The images obtained from the particle size analyzer clearly indicating that all of these cancer cell lines have majorly inner diameters of greater than 10 μm. 30,33) The values of these inner diameters are summarized in Table S2 (Figure 4b). For further analyses, we used the inner diameter as a typical parameter, because a combination of inner diameter and circularity was found to be appropriate for discriminating cancer cells from normal cells.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
“…Studies of the physical properties of CTCs found that these heterogeneous cells typically have lower buoyant densities and are larger (7-30 µm) than other hematopoietic cells [43][44][45][46][47] . Despite heterogeneity, numerous CTC isolation platforms have been developed to enrich for these rare cells from blood with notable recovery and purity rates.…”
Section: Ctc Isolation Based On Physical Propertiesmentioning
confidence: 99%
“…Changes in CTC size, surface markers, and nuclear-to-cytoplasm ratio can occur due to vesicle shedding processes, 26 the epithelial-to-mesenchymal transition (EMT) 9,11,27 in which tumor cells can be reprogrammed as cancer develops, or developed cancer therapy resistance. 28 Cell lines have been shown to be too large and expresses excessive amounts of surface markers 29,30 relative to bloodstream-captured CTCs. Such acquired differences can also result in different DEP spectra, inducing shifts in the crossover frequency.…”
Section: Introductionmentioning
confidence: 99%